Determination of Developing Constructive and Positive Conflict Resolution Mechanism Strategies at Various Organizational Levels - Mohammed, Yagana Bulama (Selected Topics in Humanities and Social Sciences Vol. 4, 2021)
Organizations develop many constructive conflict resolution mechanism strategies at various levels of the organization. The concepts of peace and conflict are inextricably related and exist side by side in accordance with the prevailing circumstances. Peace and conflicts have never prevailed at the same moment. Peace exists when there is no conflict while conflict also exists when peace is absent. Peace and conflict as a concept has been the bedrock of peace studies since its emergence as an academic discipline at local, national and international levels. Therefore better understanding of the concept of peace and conflict will further widen the horizon of students who want to embark on studies related to the concepts.